Pre-Marital Implementation Agreement by Act No. 1 of 1974 on Marriage Which Made by Notarial Deed - Sri Setiyaningsih; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2019)
The problem in this study were (1) How is the implementation of a pre-marital agreement according to Act No. 1 of 1974 on marriage made by notarial deed, (2) the constraints what emerged in the implementation of the agreement before marriage according to the Act No. 1 of 1974 on the marriage made by notarial deed, (3) How does the solution implementation constraints pre-marital agreement according to Act No. 1 of 1974 on marriage made by notarial deed. This study uses a method socio-legal approach that the research method approach a problem through a merger between the normative analysis with non-legal science approach in view of the law.The results of this study indicate that (1) Implementation of the pre-marital agreement by notary deed that under Act No. 1 of 1974 on Marriage should be undertaken in good faith by both parties that a pre-marital agreement. In a pre-marital agreement matters mentioned therein should not be contrary to public order, morality, law and religion, and an agreement was reached after both parties agreed and voluntary and no coercion. (2) Criminal cases against pre-marital agreement by notary deed pursuant to Act No. 1 of 1974 on Marriage one of which is when the parties to make pre-marital agreement deed by Notary who forget listed in the civil registry.Keywords: Pre-marital; Marriage Agreement; Notarial Deed.